Analisis Pengaruh Iklim Kerja dan Motivasi Terhadap Kinerja Pegawai: Studi Kasus pada UPTD Puskesmas di Kota Tasikmalaya - Cahyati, Peni; Hartono, Dudi; Sasmita, Anah (JUDICIOUS, 2023)
This study analyzes the influence of work climate and motivation on employee performance at the Primary Health Care Unit (UPTD Puskesmas) in Tasikmalaya City. Employee performance (Y) is affected by work climate (X1) and motivation (X2) both partially and simultaneously. However, there are dimensions within each variable that require improvement, such as leadership's responsiveness to assistance requests in the work climate and the provision of recognition in motivation. The research employs a descriptive and verificative survey method with path analysis. Findings reveal that a positive work climate fosters a conducive work environment, while strong motivation drives employees towards achieving organizational goals. Based on these findings, it can be concluded that factors of leadership, work climate, motivation, and employee performance are interrelated within the context of Primary Health Care Units, contributing to the effectiveness of primary healthcare services.